ANALISIS PENERAPAN PRINSIP AKUNTABILITAS DAN TRANSPARANSI TERHADAP PELAKSANAAN PENGELOLAAN ANGGARAN BERBASIS KINERJA (STUDI KASUS PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH KABUPATEN MUSI BANYUASIN) - Rano Asoka; Candra Romanda (Jurnal Ilmiah Akuntansi Rahmaniyah, 2022)
The purpose of this study was to determine the application of the principles of Accountability and Transparency in the Implementation of Performance-Based Budget Management at the Regional Development Planning Agency (Bappeda) of Musi Banyuasin Regency. The research method used was a qualitative method with a descriptive approach. Data collection techniques were field studies, interviews and documentation. The data analysis technique was a descriptive approach. The results of this study indicated that the Regional Development Planning Agency (Bappeda) of Musi Banyuasin Regency in implementing budget management has implemented good principles and transparency on the implementation of activities and performance achievements or activities in the Regency Regional Development Planning Agency (Bappeda) Musi Banyuasin through the official website of the Regional Development Planning Agency (Bappeda) of Musi Banyuasin Regency. The preparation of Government Agency Performance Accountability Report (LAKIP) and Accountability Report (LKPJ) are going to be the responsibility of government administration for the year.